2020
DOI: 10.3390/ma13020420
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fatigue and Healing Properties of Conventional Bitumen and Bio-Binder for Road Pavements

Abstract: The analysis of fatigue behavior of bituminous binders is a complex issue due to several time-temperature dependent phenomena which interact simultaneously, such as damage accumulation, viscoelasticity, thixotropy, and healing. The present research involves rheological measurements aimed at evaluating the fatigue behavior and compares the self-healing capability of two plain bitumen and a bio-binder obtained by partially replacing one of the plain bitumen with a renewable bio-oil. Healing potential was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This finding is consistent with other research studies, according to which fatigue life of AC containing bio-binders can even be improved [15,17]. Moreover, the results obtained in this study on AC mixes are in agreement with those found in previous studies focused exclusively on the binder phase [9,10] that showed comparable fatigue life for both the bio-binder and the reference bitumen.…”
Section: Indirect Tensile Fatigue Testsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with other research studies, according to which fatigue life of AC containing bio-binders can even be improved [15,17]. Moreover, the results obtained in this study on AC mixes are in agreement with those found in previous studies focused exclusively on the binder phase [9,10] that showed comparable fatigue life for both the bio-binder and the reference bitumen.…”
Section: Indirect Tensile Fatigue Testsupporting
confidence: 93%
“…Some research works have been conducted on performance evaluation of bio-binders from a chemical, morphological and rheological point of view. Specifically, several studies with a focus on the healing potential, fatigue behavior, as well as aging properties, demonstrated promising results, highlighting no compromising behavior or particular drawbacks and, in some cases, improved response as well [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty universities and scientific centres contributed with their original research papers to this Special Issue of Materials . The issues covered can be divided into five main topics: Characterization of recycled materials in asphalt concrete mixtures, such as waste of sanitary ceramics [ 23 ], crumb rubber (CR) from waste tires [ 24 , 25 , 26 ] and reclaimed asphalt (RA) [ 27 , 28 ]; Investigation of natural [ 28 ] or bio-based [ 29 ] materials used as rejuvenators in recycled asphalt applications; Study of rheological and fatigue behaviour of bituminous materials with [ 30 ] and without [ 31 ] the use of renewable bio-materials; Evaluation of lubricant characteristics of graphite nanoplatelets [ 32 ]; Fatigue life prediction model for materials employed on long-span steel bridge decks [ 33 ]. …”
Section: Short Description Of the Articles Published In This Special ...mentioning
confidence: 99%
“…Study of rheological and fatigue behaviour of bituminous materials with [ 30 ] and without [ 31 ] the use of renewable bio-materials;…”
Section: Short Description Of the Articles Published In This Special ...mentioning
confidence: 99%